Adult disinhibited social engagement in adoptees exposed to extreme institutional deprivation: examination of its clinical status and functional impact. (November 2017) - Kennedy, Mark; Kreppner, Jana; Knights, Nicky; Kumsta, Robert; Maughan, Barbara; Golm, Dennis; Hill, Jonathan; Rutter, Michael; Schlotz, Wolff; Sonuga-Barke, Edmund
Abstract : Background: Early-life institutional deprivation produces disinhibited social engagement (DSE). Portrayed as a childhood condition, little is known about the persistence of DSE-type behaviours into, presentation during, and their impact on, functioning in adulthood. Aims: We examine these issues in the young adult follow-up of the English and Romanian Adoptees study. Method: A total of 122 of the original 165 Romanian adoptees who had spent up to 43 months as children in Ceauşescu's Romanian orphanages and 42 UK adoptees were assessed for DSE behaviours, neurodevelopmental and mental health problems, and impairment between ages 2 and 25 years. Results: Young adult DSE behaviour was strongly associated with early childhood deprivation, with a sixfold increase for those who spent more than 6 months in institutions. However, although DSE overlapped with autism spectrum disorder and attention-deficit hyperactivity disorder symptoms it was not, in itself, related to broader patterns of mental health problems or impairments in daily functioning in young adulthood. Conclusions: DSE behaviour remained a prominent, but largely clinically benign, young adult feature of some adoptees who experienced early deprivation.